2023
DOI: 10.1021/acs.iecr.3c00879
|View full text |Cite
|
Sign up to set email alerts
|

Computational Assessment of an Amine-Based Solvent Library for High-Salinity Brine Desalination

Abstract: Human population growth has increased the demand for freshwater. Simultaneously, improvements to high-salinity brine desalination technology are needed to treat wastewater from expanding industrial activities. Temperature-swing solvent extraction (TSSE), initially proposed in the 1960s for low-salinity brine desalination, has recently been found to be effective for processing high-salinity brines. Although there have been several individual investigations performed to test the TSSE performance of various amine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…33 A better understanding of the structure of amine-water-salt mixtures can help us to develop and select solvents that optimize the balance between throughput and selectivity. 34 Similar arguments apply to the case where solvents are being used for ion extraction from water.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…33 A better understanding of the structure of amine-water-salt mixtures can help us to develop and select solvents that optimize the balance between throughput and selectivity. 34 Similar arguments apply to the case where solvents are being used for ion extraction from water.…”
Section: Discussionmentioning
confidence: 93%
“…Extending this idea, and highly relevant for understanding switchable solvents and their performance, making measurements that give insight into the structure and dynamics of local chemical environments as they respond to stimuli helps inform the selection and application of the reversible solvents. 34 The techniques developed here would be well-suited to further study of other switchable solvents, ionic liquids, deep eutectic solvents, polymers, microemulsions, supramolecular chemistries, and nanomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling fluid phase equilibria in aqueous–organic–electrolyte mixtures across a wide range of salinities are challenging given the range of complex phenomena arising from the interactions between polar solvent molecules and ions. Atomistic simulations of biphasic mixtures comprising water and salts mixed with amine-, imidazole-, , carboxylic-acid, or ionic-liquid-based solvents have shown that small, highly charged ions have a strong impact on water–solvent interactions and structure in both phases. In this study, the semiempirical electrolyte nonrandom two-liquid (eNRTL) model is used to capture the excess Gibbs free energy false( normale normalx false) of highly nonideal mixtures of water, DME, and sodium chloride (NaCl), with adjustable parameters estimated using experimental data.…”
Section: Thermodynamic Modelsmentioning
confidence: 99%